Dentistry - At the Heart of Conflict between Medicine and Technology - Claude Jaquiery (MDPI AG, 2012)
As the first Editor-in-Chief of Dentistry Journal, I would like to provide a few comments about this field of research and practice. Evolved from a purely technical profession, dentists are nowadays exposed to a variety of different challenges. [...]